Ring chromosome 20: a further contribution to the delineation of epileptic phenotype - Borković, Milan; Čuturilo, Goran; Cerovac, Natasa (Vojnosanitetski pregled, 2022)
Introduction. Ring chromosome 20 [r(20)] syndrome is a rare genetic abnormality where two arms of the 20th chromosome fuse forming a ring chromosome, resulting in intractable epilepsy and wide range of behavioral problems and cognitive deficits. Case report. We presented four patients with r (20) syndrome diagnosed between the years 2000–2018. In all patients we analyzed clinical epilepsy features (seizure semiology, seizure frequency/drug response, the presence of nonconvulsive status epilepticus), cognitive status and the phenotype characteristics. The average age of epilepsy onset was 6 years. All four patients had nocturnal epileptic events and normal brain magnetic resonance (MR) imaging. Dysmorphism was present in two children, behavioral problems also in two children and intellectual disabilities were observed in three children. R(20) syndrome mosaicism ranged between 17% and 83% of blood lymphocytes. Conclusion. Despite the small size of our group, we think that our findings have clinical relevance. Refractory childhood onset epilepsy and especially the occurrence of nocturnal epileptic events should help physicians to recognize this chromosomopathy. Routine karyotyping can be employed to identify the patients easily.